High Incidence of Refeeding Syndrome during the Transition from F75 to Ready-to-Use Therapeutic Feeds among Children 6 to 59 Months with Severe Acute Malnutrition at the Pediatric Nutritional Unit of Mulago Hospital - Wani Muzeyi; Teddy Ochieng Andra; Lorraine Oriokot; Victor Musiime (Journal of Nutrition and Metabolism)
Background. Refeeding syndrome is a complication developed by children being managed for severe acute malnutrition (SAM). It is caused by changes in electrolyte balance once high-caloric feeding is reinitiated. Phosphorus, potassium, and magnesium are the main electrolytes affected when it occurs. However, hypophosphatemia is the hallmark of the diagnosis of refeeding syndrome. WHO recommends inpatient management of patients with complicated SAM with initially F75 which is low in calories and later transitioned to RUTF which is high in calories but also has a higher phosphorus content. Objective. This study aims to determine the incidence and factors associated with refeeding syndrome in the transition phase when treating children aged 6 to 59 months with severe acute malnutrition at the Mwanamugimu Nutritional Unit, Mulago. Methods. We conducted a prospective cohort study at the Mwanamugimu Nutritional Unit of Mulago National Referral Hospital. A total of 150 children between 6 and 59 months with SAM were enrolled into the study. We measured serum electrolytes (phosphorus, sodium, and potassium) at admission, initiation of RUTF, and 48 hours after transition. The refeeding syndrome was diagnosed by a drop in serum phosphorus of more than 0.3 mmol from baseline. The data were analyzed using STATA 17.0. Incidence of refeeding syndrome was determined as the proportion of participants whose serum phosphorus declined by more than 0.3 mmol from baseline. For factors associated, a multivariate-modified Poisson regression analysis reporting relative risk was performed with a 0.2 level of significance at bivariate and 0.05 at multivariate analyses. Results. Of the 150 children recruited, 35 were lost to follow-up and 115 children had their data analyzed. Of the 115 participants in the study, 40 developed refeeding syndrome indicating a cumulative incidence of 34.8% with a 95% CI of 26.5–44%. A low baseline serum sodium (RR: 0.89, 95% CI: 0.80–0.99, and P value: 0.038) and having edematous malnutrition (RR: 0.90, 95% CI: 0.81–0.99, and P value; 0.042) at admission were found to be significant (P<0.05) risk factors of refeeding syndrome. Conclusion. The cumulative incidence of RFS of 34.8% is very high. RFS is found to be associated with low baseline sodium and pedal edema. Children with a low baseline sodium and edema should undergo a cautious transition of feeds.